The mindful moms training: development of a mindfulness-based intervention to reduce stress and overeating during pregnancy - Cassandra Vieten; Barbara A. Laraia; Jean Kristeller; Nancy Adler; Kimberly Coleman-Phox; Nicole R. Bush; Helané Wahbeh; Larissa G. Duncan; Elissa Epel (BMC, 2018)
Abstract Background Pregnancy is a time of high risk for excessive weight gain, leading to health-related consequences for mothers and offspring. Theory-based obesity interventions that target proposed mechanisms of biobehavioral change are needed, in addition to simply providing nutritional and weight gain directives. Mindfulness training is hypothesized to reduce stress and non-homeostatic eating behaviors - or eating for reasons other than hunger or caloric need. We developed a mindfulness-based intervention for high-risk, low-income overweight pregnant women over a series of iterative waves using the Obesity-Related Behavioral Intervention Trials (ORBIT) model of intervention development, and tested its effects on stress and eating behaviors. Methods Overweight pregnant women (n = 110) in their second trimester were enrolled in an 8-week group intervention. Feasibility, acceptability, and facilitator fidelity were assessed, as well as stress, depression and eating behaviors before and after the intervention. We also examined whether pre-to-post intervention changes in outcomes of well-being and eating behaviors were associated with changes in proposed mechanisms of mindfulness, acceptance, and emotion regulation. Results Participants attended a mean of 5.7 sessions (median = 7) out of 8 sessions total, and facilitator fidelity was very good. Of the women who completed class evaluations, at least half reported that each of the three class components (mindful breathing, mindful eating, and mindful movement) were "very useful," and that they used them on most days at least once a day or more. Women improved in reported levels of mindfulness, acceptance, and emotion regulation, and these increases were correlated with reductions in stress, depression, and overeating. Conclusions These findings suggest that in pregnant women at high risk for excessive weight gain, it is both feasible and effective to use mindfulness strategies taught in a group format. Further, increases in certain mindfulness skills may help with better management of stress and overeating during pregnancy. Trial registration ClinicalTrials.gov NCT01307683, March 8, 2011.